2010
DOI: 10.1016/j.ydbio.2010.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Tbx18 and Tbx15 null-like phenotypes in mouse embryos expressing Tbx6 in somitic and lateral plate mesoderm

Abstract: Members of the T-box family of transcription factors play essential roles in cell type specification, differentiation, and proliferation during embryonic development. All T-box family members share a common DNA binding domain - the T-domain - and can therefore recognize similar sequences. Consequently, T-box proteins that are co-expressed during development have the potential to compete for binding at downstream targets. In the mouse, Tbx6 is expressed in the primitive streak and presomitic mesoderm, and is sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
2
9
0
Order By: Relevance
“…Remarkably, our analysis of eBMD GWAS data (64) indicates that the TBX18 gene is also associated with eBMD. This is consistent with the partial overlap of functions and high amino acid sequence homology between TBX15 and TBX18 proteins (26,65).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Remarkably, our analysis of eBMD GWAS data (64) indicates that the TBX18 gene is also associated with eBMD. This is consistent with the partial overlap of functions and high amino acid sequence homology between TBX15 and TBX18 proteins (26,65).…”
Section: Discussionsupporting
confidence: 84%
“…The more selective nature of the index/proxy set of SNPs might be a result of the GWAS Catalog extracting the most significant SNP from each independent locus to assign index SNPs (16). We found that 38% (36) and 51% (19) of the obesity and eBMD index/proxy SNPs as well as 15% (65) and 10% (46) of the obesity and eBMD imputed SNPs in the TBX15/WARS2 region overlapped enhancer/promoter chromatin preferentially in SAT or ostb, respectively ( Fig. 2B and F; Supplementary Material, Tables S4 -S6).…”
Section: Tbx15 Enhancer or Promoter Chromatinmentioning
confidence: 91%
“…Combinatorial expression of these factors defines nascent paraxial mesoderm (T phenotype, as they all display a loss of posterior somites and PSM (Fujimoto and Yanagisawa, 1979;Chapman and Papaioannou, 1998;. However, gain-of-function studies on Tbx6 in mice (Wehn and Chapman, 2010) and T in embryonic stem cells (ESCs) (Lindsley et al, 2008) do not reveal strong mesoderm-inducing activity, raising the question as to what is the major positive regulator(s) of PSM fate.…”
Section: Introductionmentioning
confidence: 99%
“…TBX6 of the TBX family was found to participate in differentiation of posterior stem cells during embryo development 7 . The absence of TBX6 was reported to induce neural plate and somite development 8 , 9 . This implies that TBX6 regulates differentiation of posterior stem cells which form a tail in the later stages.…”
Section: Introductionmentioning
confidence: 99%